Retro‐odontoid pseudotumor with uncommon presentation of cervical spine injury - Kikuta, Shota (Acute Med Surg, 2021)
BACKGROUND: We report the first case of retro‐odontoid pseudotumor with an isolated symptom of C2–C3 dysesthesia triggered by a traumatic event. CASE PRESENTATION: An 86‐year‐old man, who was a wood craftsman for more than 50 years, presented to the emergency room with sudden‐onset severe posterior head and neck dysesthesia after accidentally falling backward. No neurological impairment of the extremities was noted. Computed tomography revealed a C2–C7 osteophyte formation, mainly in front of the vertebral bodies. Moreover, magnetic resonance imaging showed cervical spinal cord compression by a soft tissue mass posterior to the odontoid process of the axis. Therefore, we diagnosed a cervical spine injury with an isolated symptom of C2–C3 dysesthesia due to a retro‐odontoid pseudotumor. He did not undergo surgical intervention and was transferred to a rehabilitation hospital on day 11 for pain control. CONCLUSION: Our report could be useful to emergency physicians dealing with similar cases of cervical symptoms following trauma.